Empathy as a professionally significant quality of a modern blogger’s personality - O. V. Kurasova; M. V. Iontseva (Вестник университета, 2020)
This article considers empathy as a professionally significant personal quality of a modern blogger, analyses theoretical approaches of domestic and foreign researchers to the study of empathy, characterizes forms and types of empathy. The paper gives definition of blogging, describes the specifics of the blogger’s activities, taking into account the peculiarities of the online environment, and analyses the most successful bloggers of Russia. The authors describe a theoretical model of empathy and carry out an empirical study aimed at identifying professionally significant qualities of a blogger’s personality. The study considers such characteristics of a blogger as interesting content, successfulness, popularity, awareness of the topic, emotional closeness, common interests, values with subscribers and others